Environmental Literacy in Elementary School 111 Pekanbaru (A Naturalistic Inquiry Study at Adiwijaya School National Level) - Zaka Hadikusuma Ramadan; Elpri Darta Putra; Agus Baskara (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This research aims to; 1) describe the condition of the physical environment at Elementary School 111 Pekanbaru in the implementation of environmental literacy; 2) describe the implementation of Adiwiyata program at Elementary School 111 Pekanbaru in an effort to implement environmental literacy; 3) describe the learning at Elementary School 111 Pekanbaru in the effort to apply environmental literacy; and 4) describe the obstacles and solutions attempted by the schools at Elementary School 111 Pekanbaru in the implementation of environmental literacy. The method used in this study is naturalistic inquiry. The location of this study was conducted at Elementary School 111 Pekanbaru. Data collection techniques in this study are; 1) interview; 2) observation; and 3) documentation. Data analysis of the results of the study used Miles and Huberman model, namely, data reduction, data display, and drawing conclusion. The research results obtained that First, efforts to increase students' environmental literacy through the condition of the physical environment of Elementary School 111 Pekanbaru was dominated by the existence of Adiwiyata physical evidence. Second, efforts to increase environmental literacy of students in Elementary School 111 Pekanbaru through the Adiwiyata program are more dominated by the existence of Adiwiyata physical evidence and the application of an environment-based curriculum (monolithic curriculum for Environmental education subjects). Third, efforts to improve environmental literacy of students are made through learning, namely the selection of Basic Competencies in 2013 curriculum which has an environmental content and utilizes the school environment as a learning laboratory. Fourth, that is related to the obstacles encountered and the solutions pursued by Elementary School 111 Pekanbaru in an effort to increase environmental literacy of students. As for the obstacles including: accustoming students to love the environment, uniting the perspectives and goals of classroom action research, students, and parents, the solution pursued by Elementary School 111 Pekanbaru is to keep trying to accustom, give examples, give advices, provide guidance, and return to the written rules. The next obstacle is that there are still some teachers who sometimes give bad examples, the solution pursued by Elementary School 111 Pekanbaru is to inter-inspect each other related to activities in the school environment. The next obstacle is that some teachers are still trying to adjust to the implementation of 2013 curriculum, and the solution sought by Elementary School 111 Pekanbaru is to interact, learn and ask more experienced teachers.